Revisiting Character Education from Islamic Perspective: A Quest for Character-based Education in Indonesia - Eka Eka (Ulumuna, 2017)
Since it was launched in 2010, Character Education is becoming a mesmerizing framework which is assumed to bring about the changes in Indonesian national education. Especially, National Education Framework for Character Education 2010 is agreed to be a guide for national education success in building nation character of the youngsters. However, such a dual-system of education—general and Islamic education, that is embraced in the current national education system emanates various Character Education both its interpretation and implementation. The discussion in this paper highlights that from various definitions and interpretations, character education practices deals with definite values rather than relative values. Islam world has many sources of values and ethics and thus Muslim educators and teachers are suggested to base the values inculcation to students on the Islamic sources of values and ethics. Undesired changes of society’s life caused by secualrism, personalism, pluralism, etc., make character education practices as necessary to conduct in order to counter those ideologies.